Effect of Transcranial Direct Current Stimulation on Performance of Basketball two Point Field Throws in Skilled Basketball Players - Zahra Naghizadeh; Ahmadreza Movahedi; Mahdi Namazizadeh; Motahareh Mirdamadi (University of Tehran, 2020)
The Effect of transcranial direct current stimulation (tDCS) has been studied in descriptive and laboratory tasks in the field of motor and sport skills. It is necessary that tDCS effects on real sport skills are investigated. The aim of the current study was to examine the Effect of tDCS on performance of basketball two point field throws (BFT) in skilled basketball players. In this quasi- experimental study, we used a repeated measure design including a pretest, intervention, posttest and follow. A total of 26 male basketball players were randomly divided into either an experimental or a sham group. Both groups watched the point light model of the performance of two elite basketball players. Then, the participants of the exercise group received tDCS over their pre-motor cortex for 20 minutes. The participants of the sham group underwent identical tasks performance except that tDCS was artificially applied for them. BFT was assessed at baseline (pre-intervention), one day post-intervention and 7 days post-intervention. For analyzing data, two factor Mixed model ANOVA, independent and paired t-tests were used. Results showed that anodal tDCS created no between group's differences in BFT in the intervention phase while tDCS lead to significant improvement of BFT in experimental group skills compared to sham group in test phase. Results showed that tDCS could be considered as a useful intervention for the improvement of BFT in skilled basketball players.